Magic and religion in the ancient Mediterranean world
1 online resource
Keywords: "This volume explores aspects of ancient magic and religion in the ancient Mediterranean, specifically ways in which religious and mythical ideas, including the knowledge and practice of magic, were transmitted and adapted through time and across Greco-Roman, Near Eastern, and Egyptian cultures. Offering an original and innovative combination of case studies on the material aspects and cross-cultural transfers of magic and religion, this book brings together a range of contributions that cross and connect sub-fields with a pan-Mediterranean, comparative scope. Section I investigates the material aspects of magical practices, including first editions and original studies on papyri, gems, lamellae containing binding curses and protective texts, and other textual media in ancient book culture. Several chapters feature the Greco-Egyptian Magical Papyri, the compilation of magical recipes in the formularies, and the role of physical book-forms in the transmission of magical knowledge. Section II explores magic and religion as nodes of cultural exchange in the ancient Mediterranean. Case studies range from Egypt to Anatolia and from Syria-Phoenicia to Sicily, with Greco-Roman religion and myth integrated in a diverse and interconnected Mediterranean landscape. Readers encounter studies featuring charismatic figures of Magi and itinerant begging priests, the multiple understandings of deities such as Hekate, Herakles, or Aphrodite, or the perceived exotic origin of cult statues, mummies, amulets, and cursing formulae, which bring to light the rich intercultural networks of the ancient Mediterranean, and the crucial role of magic and religion in the process of cross-cultural adaptation and innovation. Magic and Religion in the Ancient Mediterranean World appeals to both specialized and non-specialized audiences, with expert contributions written in an accessible way. This is a fascinating resource for students and scholars working on magic, religion, and mythology in the ancient Mediterranean"--